JIEYUANSHEN DECOCTION EXERTS ANTIDEPRESSANT EFFECTS ON DEPRESSIVE RAT MODEL VIA REGULATING HPA AXIS AND THE LEVEL OF AMINO ACIDS NEUROTRANSMITTER - qiuxia, Zhang; xinlong, Ma; yilong, Yang; hui, Zhao; yali, Wang; xiaoquan, Yao; lei, Wang; jiahui, Chang; haiyan, Zou (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Jieyuanshen decoction (JYAS-D) - a traditional Chinese medicine was invented by Professor Nie basedon classic formulas, chaihu jia longgu muli decoction has been proved as having favorable curative effects ondepression in clinical practices. The aim of this study was to investigate the antidepressant effects and its molecularmechanism of JYAS-D.Materials and Methods: The model of depression was established by Chronic Unpredictable Stress. Different doses(8.2 g/kg, 16.3 g/kg, 32.7 g/kg) of JYAS-D was orally administered; Fluoxetine was orally administered with 10mg/kg.All treatments lasted for 28 days. Sucrose preference and open-field tests were adopted to observe the behavior of rats.OPA (ortho-phthalaldehyde) derivatization method was used to detect the contents of amino acid neurotransmitter. RIA(Radiation immunity analysis) method was used to measure the serum concentrations of CORT (Corticosterone),ACTH (Adrenocorticotropic hormone) and CRH (Corticotropin-releasing hormone). ELISA (Enzyme linkedimmunosorbent assay) method was adopted to examine the contents of Glucocorticoid receptor (GR) andMineralocorticoid receptor (MR) in hippocampus.Results: Compared with the model group, sucrose preference was increased in all treatment groups. The concentrationof serum CORT was reduced in the middle dose of JYAS-D and control groups; the concentration of serum ACTH wasreduced in the low and high-dose of JYAS-D; the concentration of serum CRH was reduced in the middle andhigh-dose of JYAS-D. The content of hippocampus GR was increased in the middle and high-dose of JYAS-D; thecontent of hippocampus Glu (Glutamic acid) was reduced among the low, middle and high-dose of JYAS-D andfluoxetine group, the ratio of Glu/γ-GABA (γ-aminobutyric acid was reduced in the low and high-dose of JYAS-D.Conclusion: JYAS-D had a significant antidepressant-like effect on rat model through regulating serum concentrationof CORT, ACTH and CRH, increasing the content of hippocampus GR and regulating the equilibrium of amino acidsneurotransmitter.